Real-World Clinical Experience With Idebenone in the Treatment of Leber Hereditary Optic Neuropathy. Issue 4 (December 2020) - Catarino, Claudia B.; von Livonius, Bettina; Priglinger, Claudia; Banik, Rudrani; Matloob, Selma; Tamhankar, Madhura A.; Castillo, Lorena; Friedburg, Christoph; Halfpenny, Christopher A.; Lincoln, John A.; Traber, Ghislaine L.; Acaroglu, Gölge; et al.
Abstract : Background: Leber hereditary optic neuropathy (LHON) leads to bilateral central vision loss. In a clinical trial setting, idebenone has been shown to be safe and to provide a trend toward improved visual acuity, but long-term evidence of effectiveness in real-world clinical practice is sparse. Methods: Open-label, multicenter, retrospective, noncontrolled analysis of long-term visual acuity and safety in 111 LHON patients treated with idebenone (900 mg/day) in an expanded access program. Eligible patients had a confirmed mitochondrial DNA mutation and had experienced the onset of symptoms (most recent eye) within 1 year before enrollment. Data on visual acuity and adverse events were collected as per normal clinical practice. Efficacy was assessed as the proportion of patients with either a clinically relevant recovery (CRR) or a clinically relevant stabilization (CRS) of visual acuity. In the case of CRR, time to and magnitude of recovery over the course of time were also assessed. Results: At time of analysis, 87 patients had provided longitudinal efficacy data. Average treatment duration was 25.6 months. CRR was observed in 46.0% of patients. Analysis of treatment effect by duration showed that the proportion of patients with recovery and the magnitude of recovery increased with treatment duration. Average gain in best-corrected visual acuity for responders was 0.72 logarithm of the minimal angle of resolution (logMAR), equivalent to more than 7 lines on the Early Treatment Diabetic Retinopathy Study (ETDRS) chart. Furthermore, 50% of patients who had a visual acuity below 1.0 logMAR in at least one eye at initiation of treatment successfully maintained their vision below this threshold by last observation. Idebenone was well tolerated, with most adverse events classified as minor. Conclusions: These data demonstrate the benefit of idebenone treatment in recovering lost vision and maintaining good residual vision in a real-world setting. Together, these findings indicate that idebenone treatment should be initiated early and be maintained more than 24 months to maximize efficacy. Safety results were consistent with the known safety profile of idebenone. Abstract : Supplemental Digital Content is Available in the Text. Idebenone treatment can result in both stabilization of residual visual acuity and recovery of lost vision, with a treatment duration of at least 2 years needed to maximize the probability of recovery.